PENGARUH MODEL PEMBELAJARAN KONFLIK KOGNITIF TERHADAP PENINGKATAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS XI - Asep Sujana; Enjuh Juhaedi (UJMES (Uninus Journal of Mathematics Education and Science), 2017)
This research is intended to know the extent of the influence of the application of Cognitive Conflict Learning Model to Improving Mathematical Understanding of Students of Class XI IPS SMA Mathla'ul Anwar Menes "On the Subject of Opportunity in the School Year 2014/2015. The method used in this study is the experimental method is the only research method that is considered the most appropriate to test the hypothesis about causality. The instrument used in the form of concept comprehension skills tests related to the material already taught. Data analysis used in this research is gain test and t test. From the result of gain value achieved by each class that is, for experimental class gain value 0,49 and control class gain value 0,36, while for result of t test from result of postest is t-analyze = 10,01 and t-table value = 1,902. By comparing it to t-analyze to t-table = 10.01 1.902; H0 rejected and Ha accepted. This means that there is a difference in the ability of students to understand the concept of mathematics between using learning model of Cognitive Conflict compared with conventional learning.